2021
DOI: 10.1302/2633-1462.25.bjo-2020-0176.r1
|View full text |Cite
|
Sign up to set email alerts
|

Embracing virtual outpatient clinics in the era of COVID-19

Abstract: The response to the COVID-19 pandemic has raised the profile and level of interest in the use, acceptability, safety, and effectiveness of virtual outpatient consultations and telemedicine. These models of care are not new but a number of challenges have so far hindered widespread take-up and endorsement of these ways of working. With the response to the COVID-19 pandemic, remote and virtual working and consultation have become the default. This paper explores our experience of and learning from virtual and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The implementation of VFC increased remote delivery of care, which has proven to be an efficient, cost-effective and satisfactory alternative to face-to-face care (Ekeland et al., 2010; Graham et al., 2021; Haider et al., 2022; Lee et al., 2021; Thatcher et al., 2021). Other studies on VFC protocols have reported similar results (Brogan et al., 2017; Davey et al., 2020; Dunkerley et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The implementation of VFC increased remote delivery of care, which has proven to be an efficient, cost-effective and satisfactory alternative to face-to-face care (Ekeland et al., 2010; Graham et al., 2021; Haider et al., 2022; Lee et al., 2021; Thatcher et al., 2021). Other studies on VFC protocols have reported similar results (Brogan et al., 2017; Davey et al., 2020; Dunkerley et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This streamlines patient care, allowing them to receive appropriate treatment in a timely and convenient manner. 43,44 Lee et al 45 reported that regular engagement with key stakeholders (patients/clinicians/primary care physicians/ED physicians) and acting upon feedback led to effective triage of hand and wrist injuries. The team found that clear communication with patients and staff education resulted in rapid expansion of virtual services to all groups of patients with fractures during the pandemic.…”
Section: Unsuitable For Certain Population Groups Effective Triagingmentioning
confidence: 99%